2021
DOI: 10.31557/apjcp.2021.22.2.517
|View full text |Cite
|
Sign up to set email alerts
|

Cancer, Mortality, and Acute Kidney Injury among Hospitalized Patients with SARS-CoV-2 Infection

Abstract: Background: To evaluate Coronavirus Disease 2019-(COVID19) patients treated within our academic medical system to determine if history of malignancy, both in general and specifically in genitourinary oncology patients, is associated with adverse clinical outcomes, including acute kidney injury (AKI) and mortality. Methods: We conducted a retrospective cohort study among patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in a multi-hospital, academic medical instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The initial search retrieved 171 articles for review ( Figure 1 ). After the inclusion of records that were identified through additional sources and the removal of duplicate articles, a total of 29 studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] were included in this systematic review and meta-analysis. Except for the series by Wang et al, which included patients who received anti-COVID vaccines, all other series had their observation period in the pre-vaccine months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search retrieved 171 articles for review ( Figure 1 ). After the inclusion of records that were identified through additional sources and the removal of duplicate articles, a total of 29 studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] were included in this systematic review and meta-analysis. Except for the series by Wang et al, which included patients who received anti-COVID vaccines, all other series had their observation period in the pre-vaccine months.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies [ 13 , 17 , 23 , 24 , 25 , 27 , 31 , 36 , 37 ] reported the risk of severe infection (life-threatening or requiring ICU admission/mechanical ventilation) in patients with lung cancer compared to non-lung cancer patients. Lung cancer diagnosis increased the risk of severe disease (HR = 1.47 [95%CI1.06, 2.03], p = 0.02; Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the difference could partially be explained by the heterogeneities in region or patient population, other possibilities might also contribute, such as different AKI diagnostic criteria used (biochemical or coded diagnosis), hospital setting (academic center or regional hospital) and the specific definitions of relevant terms (such as baseline creatinine) ( 49 , 50 ). As the pandemic goes on, the health-care community gained better understanding on the disease and are more sophisticated in treatment which might contribute to a drop of AKI and RRT rates over time ( 51 , 52 ). More importantly, different research groups recently reported Omicron demonstrated lower replication in lower airway organoids, lung cells and gut cells.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason behind this sudden and severe systemic pathogenesis is not yet clear as in addition to the severe pulmonary "cytokine storm" 12,13 a novel hematological syndrome manifested as vascular endothelial damage, complement activation, and thrombosis, seriously compromising circulatory functions is also gaining strong acceptance 15 Vascular damage leading to pulmonary hypertension, chronic obstructive pulmonary disease, congestive heart failure, myocardial injury, and pulmonary embolism is postulated to generate respiratory syndrome. 16 Other pathological or malignant conditions, not affecting pulmonary functions, do not appear to affect Covid-19 prompted mortalities. 17 Just after virus infection in the nasal cavity, virus multiplies vigorously in the nasal mucosa, destroys cells and liberates huge quantities of free virus particles on the nasal surface.…”
Section: Introductionmentioning
confidence: 99%